МАСТЕРСТВО ШУХРАТА СОЗДАВАТЬ БАСНИ И САТИРИЧЕСКИЕ СТИХОТВОРЕНИЕ (Scientific journal of the Fergana State University, 2023)
This article is devoted to the issue of analysis and interpretation of parable and comic poems, which included the work of the poet of the 20th century and adibi Fame. The article reveals the specific features of the parable and the comic poem. The ideological content, educational and educational significance of the poet's parable” The Fox and the rabbit “and” the Frog " are analyzed line by line. The sense – thought – idea chain in the parables is shown. The comic poems “was a wolf, became a Fox” and “pale fly”, in which the expression of enlightened ideas of Fame is interpreted, are shown to reveal the vice inherent in human nature, the weaknesses, defects, flaws, incorrect behavior through a clear, sharp comic. It has been proven that the above parable and comic poems of the poet serve to educate humanity as an important tool of didactic education. It is established that the parable and comic poems of Fame fully retain their significance even now, with their spiritual example in the literary field of the XX century.